Mosque as the Center of Civilization: The Transformation of the Social Function of Mosques from the Time of the Prophet to the Modern Era of Urbanization - Syafi’i, Akhmad (Sekolah Tinggi Agama Islam Kuningan, 2025)
Mosques have a central position in the history of Islamic civilization as multifunctional institutions that not only act as places of worship, but also as centers of education, social, economic, and government. However, the times, especially in the context of modern urbanization, have led to a significant transformation of these functions. This study aims to describe and analyze the changes in the social function of the mosque from the time of the Prophet to the modern urban era, identify the factors that influence it, and offer strategies for revitalizing the mosque's function as a center of civilization. This research uses a descriptive qualitative approach with multiple case study design and thematic analysis and historical comparative methods. Data were obtained through in-depth interviews, participatory observation, and document analysis from four representative mosques in various eras and regions. The results show that the social function of mosques has experienced fragmentation due to changes in social and political structures. Nevertheless, mosques still have great potential as centers of social transformation, if supported by participatory governance, program digitalization, and community orientation. The findings show the importance of reintegrating the mosque's function as a spiritual and social public space that is adaptive to the dynamics of contemporary urban society. This study contributes to the conceptual and practical development of mosque management based on history and the needs of the times.